Drugs on the dark net: how cryptomarkets are transforming the global trade in illicit drugs - Martin, James (Palgrave Pivot, 2014)
"Drugs on the Dark Net explores the rapidly expanding world of online illicit drug trading. Following the closure of the infamous online drugs bazaar Silk Road, a new generation of cryptomarkets may now be found thriving amongst the hidden corners of the internet. Defying the world's most powerful law enforcement agencies, these encrypted websites facilitate distribution networks that reach around the globe, and are capable of delivering any type of illicit drug directly to your front door.This original criminological research offers an in-depth and non-technical account of the online illicit drugs trade. Cryptomarkets are revealed to be sophisticated hubs of commercial innovation, as well as resilient online communities of black marketeers, drug consumers and political activists. Analysis of online distribution networks indicates that they are highly efficient, extraordinarily difficult to police and, intriguingly, have the potential to reduce much of the systemic violence associated with the illicit drugs trade.Examining the future of the illicit drugs trade and the new digital front in the 'war on drugs', this study provides a timely and insightful contribution to our understanding of illicit drugs, technology and cybercrime"--